2011
DOI: 10.1093/forestry/cpr067
|View full text |Cite
|
Sign up to set email alerts
|

A broad-scale analysis of the main factors determining the current structure and understory composition of Catalonian sub-alpine (Pinus uncinata Ram.) forests

Abstract: A broad-scale analysis of the main factors determining the current structure and understory composition of Catalonian sub-alpine (Pinus uncinata Ram.) forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…In the particular case of black pine, which is considered one of the most shade-tolerant European pine species (Niinemets and Valladares, 2006), our models put the optimum CO for pine seedlings at around 30-35%, which is higher than the CO preferred by oak seedlings. Changes in land-use practices over the past few decades have notably affected the structure of most pine stands (Montes et al, 2005;Martin-Alcon et al, 2012) and may have worsened the conditions for their regeneration. In our study area, for example, we found higher pine seedlings in stands with a high presence of big trees (with dbh > 27.5 cm) but low basal area values.…”
Section: Factors Behind Pine Retreatmentioning
confidence: 99%
“…In the particular case of black pine, which is considered one of the most shade-tolerant European pine species (Niinemets and Valladares, 2006), our models put the optimum CO for pine seedlings at around 30-35%, which is higher than the CO preferred by oak seedlings. Changes in land-use practices over the past few decades have notably affected the structure of most pine stands (Montes et al, 2005;Martin-Alcon et al, 2012) and may have worsened the conditions for their regeneration. In our study area, for example, we found higher pine seedlings in stands with a high presence of big trees (with dbh > 27.5 cm) but low basal area values.…”
Section: Factors Behind Pine Retreatmentioning
confidence: 99%
“…However, forests in the Pyrenees seldom suffer from damage linked to large extreme disturbances, these being important in only a few dispersed specific locations (López-Moreno et al 2008;Muntán et al 2009). Another limitation arising from our study is that although high resolution data was found to be extremely useful for defining the current forest structure, it was not accurate enough to provide information on standing deadwood, an important variable to define a stand's structural heterogeneity (Pesonen et al 2008;Martín-Alcón et al 2012). However, our study presented some limitations.…”
Section: Discussionmentioning
confidence: 98%
“…The variables were chosen according to previous studies (Reque and Bravo 2008;Martín-Alcón et al 2012), as meaningful and non-redundant in terms of information: tree canopy cover, basal area, mean diameter, tree recruitment, and the percentages of fine wood and thick wood, and the relative difference between dominant height and mean height. The variables were chosen according to previous studies (Reque and Bravo 2008;Martín-Alcón et al 2012), as meaningful and non-redundant in terms of information: tree canopy cover, basal area, mean diameter, tree recruitment, and the percentages of fine wood and thick wood, and the relative difference between dominant height and mean height.…”
Section: Forest Structural Typologymentioning
confidence: 99%
“…Contra lo que cabría esperar, es decir, que las estructuras surgieran más disgregadas y con menor espesura conforme se aproximan al límite del bosque (timberline), en nuestro caso no se manifiesta esa relación (aunque en Andorra la correlación sea más alta que en Cataluña). De ello puede deducirse que, además del gradiente altitudinal, otros factores microestacionales (pendiente y temperatura media invernal (Martín-Alcón et al, 2012)), y/o antrópicos (actividad pecuaria o intensidad de aprovechamientos de madera), inciden severamente, no sólo en la estructura del ecotono bosque-pasto (Camarero y Gutiérrez, 2002), sino también sobre la espesura de todas las masas de pino negro localizadas por encima de 1.800 m. Se observa, asimismo, que en los Pirineos catalanes el límite altitudinal del arbolado se distribuye de modo más uniforme y constante.…”
Section: Estructura De La Masaunclassified